A phase II study of bortezomib added to rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone in patients with previously untreated indolent non‐Hodgkin's lymphoma. (7th August 2015) - Cohen, Jonathon B.; Switchenko, Jeffrey M.; Koff, Jean L.; Sinha, Rajni; Kaufman, Jonathan L.; Khoury, H. Jean; Bumpers, Nassoma; Colbert, Amanda; Hutchison‐Rzepka, Amanda; Nastoupil, Loretta J.; Heffner, Leonard T.; Langston, Amelia A.; et al.
Summary: Bortezomib‐containing combinations are active in non‐Hodgkin lymphoma (NHL) although peripheral neuropathy can limit their dose intensity. Based on our phase I findings, we conducted a phase II trial of bortezomib in combination with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) with a modified dose of vincristine. Patients with untreated indolent NHL received bortezomib (1·6 mg/m 2 ) on days 1 and 8 of a 21‐day cycle for up to 8 cycles and R‐CHOP with a 1·5 mg cap of vincristine. Patients achieving a complete response (CR) received maintenance rituximab, and remaining patients received maintenance rituximab and bortezomib. The primary endpoint was CR rate; secondary survival analyses were evaluated using the Kaplan–Meier method. Among 29 eligible patients, NHL morphologies included follicular ( n  = 20), marginal zone ( n  = 5) and small lymphocytic lymphoma ( n  = 4). Nineteen patients had CR (66%) and 10 had partial response (34%), yielding a 100% overall response rate. With a median follow‐up of 48·7 months, the 4‐year progression‐free and overall survivals were 83% and 93%. Twenty‐two patients experienced peripheral neuropathy of any grade, and two had grade 3 neuropathy. The combination of bortezomib with R‐CHOP is effective for indolent NHL, and we plan to evaluate therapies incorporating novel proteasome inhibitors in future studies in NHL.